The Timing of Strike-Slip Deformation Along the Storstrømmen Shear Zone, Greenland Caledonides: U–Pb Zircon and Titanite Geochronology - Hallett, Benjamin; McClelland, William; Gilotti, Jane (Geoscience Canada, 2014)
The Storstrømmen shear zone (SSZ) in the Greenland Caledonides is widely interpreted to have formed in a transpressional regime during sinistral, oblique collision between Baltica and Laurentia in the Silurian to Devonian. New mapping of the SSZ at Sanddal documents a 100 m thick, greenschistfacies mylonite zone cutting the eclogite to amphibolite-facies gneiss complex. We present U–Pb ion probe geochronology on zircon and titanite from a variety of lithologies that shows the SSZ was active from late Devonian to the Carboniferous (at least until 350 Ma). The age of thrusting in the foreland is not well known, but must be younger than the age of eclogite-facies metamorphism at ~400 Ma. It is, therefore, possible that contraction is the same age as strike-slip motion, and that transpression is a viable model. The timing of the SSZ is synchronous with dextral strike-slip displacement on the Germania Land deformation zone. Simultaneous displacement on sinistral and dextral, conjugate shear zones suggests that the SSZ is part of a strikeslip fault system that led to lateral escape of material northward (present day coordinates) during the waning stages of plate convergence between Laurentia and Baltica.